(untitled) (Journal of Asian Development Studies, 2024)
According to WHO, Prolonged Grief Disorder (PGD)is a potentially disabling condition that affects approximately 10% of suffering people. Narrative therapy is effective in treating prolonged grief disorder. This study aimed to investigate the efficacy of narrative therapy for those suffering from prolonged grief disorder. Data was collected by using semi-structured interviews consisting of four therapy sessions over a follow-up of four months using a qualitative research methodology with two participants who were purposefully sampled and had been diagnosed with prolonged grief disorder. Both clients showed improvement after four follow-up sessions. Client 1 reported good progress, showing the core narratives of loss, emotional regulation, and positive transformation. In the process of externalization techniques and homework, such as letter writing, she reported having better emotional health or a new perspective. Client 2 also reported to have benefited from the therapy, but she had faced more profound challenges, such as self-blame and suicidal ideation, requiring psychiatric referral. The outcomes demonstrated that narrative therapy is very effective in managing prolonged grief disorder.